2017
DOI: 10.1515/aee-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

A new algebraic LQR weight selection algorithm for tracking control of 2 DoF torsion system

Abstract: This paper proposes a novel linear quadratic regulator (LQR) weight selection algorithm by synthesizing the algebraic Riccati equation (ARE) with the Lagrange multiplier method for command following applications of a 2 degree of freedom (DoF) torsion system. The optimal performance of LQR greatly depends on the elements of weighting matrices Q and R. However, normally these weighting matrices are chosen by a trial and error approach which is not only time consuming but cumbersome. Hence, to address this issue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Here, Q and R are the weighted matrices that indicate the importance of the state and control variables in the minimization process (Elumalai and Subramanian, 2017;Oliveira et al, 2015). Moreover, the equivalent critical damping method called ECD determines the actuator force by applying the critical damping theory to the first vibration's mode (Alamatian and Rezaeepazhand, 2011;Karimpour et al, 2014)…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Here, Q and R are the weighted matrices that indicate the importance of the state and control variables in the minimization process (Elumalai and Subramanian, 2017;Oliveira et al, 2015). Moreover, the equivalent critical damping method called ECD determines the actuator force by applying the critical damping theory to the first vibration's mode (Alamatian and Rezaeepazhand, 2011;Karimpour et al, 2014)…”
Section: Numerical Examplesmentioning
confidence: 99%
“…For example, Kohiyama et al presented a method that estimates the responses for the MDOF model by using the complex-complete-quadratic-combination (CCQC) method [5]. Elumalai et al have shown the weighting matrices can be yielded by solving the inverse problem for MDOF models [6]. However, if a building model is high-DOF system, many damping ratios and natural frequencies have to be chosen to calculate the weighting matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The desired performance can generally be represented by using damping ratio and natural frequency in second-order system for Single-Input-Single-Output (SISO) systems. Elumalai & Subramanian (2017) proposed the method to select the weight matrix by synthesizing the Algebraic Riccati Equation (ARE) with the Lagrange multiplier method. However, the calculation of synthesizing must be done for each model, because a coefficient matrix is different for each model.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous research for weight tuning algorithm used algebraic calculation, Particle Swarm Optimization(PSO), Genetic Algorithm(GA), and Simultaneous Perturbation Stochastic Approximation (SPSA). Elumalai & Subramanian (2017) selected the weight matrix using algebraic calculation, but only targeted SISO systems. Tuning LQR using PSO algorithm provides better performance than PID controller.…”
Section: Introductionmentioning
confidence: 99%